Colonoscopy quality across Europe: a report of the European Colonoscopy Quality Investigation (ECQI) Group - Spada, Cristiano; Koulaouzidis, Anastasios; Hassan, Cesare; Amaro, Pedro; Agrawal, Anurag; Brink, Lene; Fischbach, Wolfgang; Hünger, Matthias; Jover, Rodrigo; Kinnunen, Urpo; Ono, Akiko; Patai, Árpad; Pecere, Silvia; Petruzziello, Lucio; Riemann, Jürgen F.; Amlani, Bharat; Staines, Harry; Stringer, Ann L.; Toth, Ervin; Antonelli, Giulio; Fuccio, Lorenzo (Endoscopy International Open, 2021)
Background and study aims The European Colonoscopy Quality Investigation (ECQI) Group comprises expert colonoscopists and investigators with the aim of raising colonoscopy standards. We assessed the levels of monitoring and achievement of European Society of Gastrointestinal Endoscopy (ESGE) performance measures (PMs) across Europe using responses to the ECQI questionnaires. Methods The questionnaire comprises three forms: institution and practitioner questionnaires are completed once; a procedure questionnaire is completed on multiple occasions for individual total colonoscopies. ESGE PMs were approximated as closely as possible from the data collected via the procedure questionnaire. Procedure data could provide rate of adequate bowel preparation, cecal intubation rate (CIR), withdrawal time, polyp detection rate (PDR), and tattooing resection sites.Results We evaluated ECQI questionnaire data collected between June 2016 and April 2018, comprising 91 practitioner and 52 institution questionnaires. A total of 6445 completed procedure forms were received.Institution and practitioner responses indicate that routine recording of PMs is not widespread: adenoma detection rate (ADR) is routinely recorded in 29 % of institutions and by 34 % of practitioners; PDR by 42 % and 47 %, CIR by 62 % and 64 %, bowel preparation quality by 56 % and 76 %, respectively.Procedure data showed a rate of adequate bowel preparation of 84.2 %, CIR 73.4 %, PDR 40.5 %, mean withdrawal time 7.8 minutes and 12.2 % of procedures with possible removal of a non-pedunculated lesion ≥ 20 mm reporting tattooing.Conclusions Our findings clearly show areas in need of quality improvement and the importance of promoting quality monitoring throughout the colonoscopy procedure.